Civil Remedies for Environmental Damage: Exploring the Effectiveness of Carbon Trading as a Tool for Restoration in Indonesia - Rahmawati, Diah Ayu; Haryono, Haryono; Endarto, Budi; Soraya, Joice; Munawaroh, Siti (The Easta Journal Law and Human Rights, 2025)
This paper discusses the effectiveness of carbon trading as a civil remedy for environmental damage in Indonesia through a juridical normative analysis. The research explores Indonesia's legal framework governing carbon trading, its implementation, and its alignment with principles such as "polluter pays" and sustainable development. The key findings profile the potential of carbon trading in financing environmental restoration, for example, reforestation and peatland rehabilitation, but are faced by challenges such as regulatory gaps, low institutional capacity, and issues of transparency. This study calls for integration of legislative reforms, increased oversight, and coordination from all stakeholders toward the best implementation of carbon trading for environmental degradation. Coupling carbon trading with civil liability mechanisms is advanced here as a means to enhance accountability and restoration outcomes.